DIFFRACTION OF LOVE WAVE IN THE MEDIUM WITH PIECEWISE HOMOGENEOUS ELASTIC INFINITE INCLUSION - Voskanyan, A. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2007)
Diffraction of Love Wave in elastic medium is considered from the boundary, where two semi-infinite elastic layers are departed. The problem is brought to the solution of Viener–Hopf functional equation due to Furie transformators of contact stress amplitudes Asymptotic formulas are obtained for contact stress amplitudes in the farther zone and in the departing of thin layers.